Answer:
m<1
Explanation:
If the expression is in the form of
, then the condition for having 2 different real roots is
.
The given expression is
.
Here, a=1, b=-2 and c=m.
So, by using equation (i),
![(-2)^2-4(1)(m)>0](https://img.qammunity.org/2021/formulas/mathematics/high-school/65dgf75nf2yoft4n9mm5mskq2gijib33z5.png)
![\Rightarrow 4-4m>0](https://img.qammunity.org/2021/formulas/mathematics/high-school/llx2e8z57somrppno8ck2ho1934iy497v8.png)
![\Rightarrow 4m<4](https://img.qammunity.org/2021/formulas/mathematics/high-school/npprwty67vz9ldj4cavetq2wfc1t66mlh9.png)
![\Rightarrow m<4/4](https://img.qammunity.org/2021/formulas/mathematics/high-school/kyo84rh3mbfi9zqa3d1e1o1b9075189pzb.png)
.
Hence, the condition for the expression
to have two different real roots is m<1.